Fabrication of TiO2 Crystalline Coatings by Combining Ti-6Al-4V Anodic Oxidation and Heat Treatments - María Laura Vera; Mario Roberto Rosenberger; Carlos Enrique Schvezov; Alicia Esther Ares (International Journal of Biomaterials)
The bio- and hemocompatibility of titanium alloys are due to the formation of a TiO2 layer. This natural oxide may have fissures which are detrimental to its properties. Anodic oxidation is used to obtain thicker films. By means of this technique, at low voltages oxidation, amorphous and low roughness coatings are obtained, while, above a certain voltage, crystalline and porous coatings are obtained. According to the literature, the crystalline phases of TiO2, anatase, and rutile would present greater biocompatibility than the amorphous phase. On the other hand, for hemocompatible applications, smooth and homogeneous surfaces are required. One way to obtain crystalline and homogeneous coatings is by heat treatments after anodic oxidation. The aim of this study is to evaluate the influence of heat treatments on the thickness, morphology, and crystalline structure of the TiO2 anodic coatings. The characterization was performed by optical and scanning electron microscopy, X-ray diffraction, and X-ray reflectometry. Coatings with different colors of interference were obtained. There were no significant changes in the surface morphology and roughness after heat treatment of 500°C. Heat treated coatings have different proportions of the crystalline phases, depending on the voltage of anodic oxidation and the temperature of the heat treatment.